REFLEKSI NILAI KEMANUSIAAN DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER DALAM KELAS PANCASILA 41 - Putra, Dzaky Wajendra Kusuma; Ratna Endang Widuatie; Anindya Florean Arkananta; Nasywa Kirana; Adrian Haris Maulana; Chelsea Amara Ariyanto (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Indonesian literature plays an important role in instilling human values, particularly through works that address social issues and justice. Pramoedya Ananta Toer’s novel Bumi Manusia, set in the era of Dutch colonial rule in the East Indies, portrays human conflicts such as racial discrimination, legal injustice, and the oppression of indigenous people. This article analyzes the implementation of the value of "A Just and Civilized Humanity" as the second principle of Pancasila through the novel Bumi Manusia in Pancasila education. The research employs a descriptive qualitative approach with methods of literary document analysis, literature review, and observation of student learning. The results of the analysis show that the novel embodies human values including equality, respect for human dignity, social justice, courage to fight oppression, and tolerance. Characters such as Minke, Nyai Ontosoroh, and Annelies represent the struggle to uphold human dignity. Through deep reflection on the characters and conflicts in the novel, students are able to identify the relevance of Pancasila values in the context of national and societal life in the modern era. In conclusion, integrating literary works into Pancasila education opens a space for critical dialogue on the application of human values, enabling students not only to understand Pancasila theoretically but also to apply it as an ethical guide in addressing contemporary humanitarian challenges.